P1092Syncope in the emergency department: can 24-hour holter monitoring be of any help?. (18th June 2020) - Lopes, J; Saleiro, C; Campos, D; Sousa, J; Puga, L; Gomes, R; Ribeiro, J; Silva, J; Goncalves, L
Abstract: Background   Syncope is a very common reason for presenting to the emergency department (ED). The existence of a telemetry unit is crucial but it is not the reality in some hospitals. In order to avoid unnecessary ward admission, 24-hour Holter (24HH) monitoring could be useful to help with the diagnosis (when the arrhythmic etiology is suspected and the symptoms are frequent enough) and also be important to safely discharge a patient.  Purpose   The purpose of this study is to evaluate the diagnostic performance of 24HH monitoring, during a syncope episode in the ER, and to compare the readmission rates between patients with normal and abnormal not diagnostic 24HH monitoring.  Methods   A cohort study of consecutive patients (P) who were monitored with 24HH in one hospital in the ED, between January 2015 and December 2017, were included. All the 24HH results were seen by a senior cardiologist and divided in three groups: A - normal, B - abnormal Holter study unlikely to explain syncope and C- Holter study considered to be diagnostic.  Groups A and B were compared using chi-square independence test to evaluate association between the result of the 24HH and readmission rates at 30 days and 1 year, as well as mortality and device implantation at 1 year. Multivariate logistic regression was used to look for other confounders.  Results   A total of 111 P were included in this study. Mean age was 75 ± 14 years old, with 55.6% male patients.  A previous emergency episode with syncope was present in 56.9% of P. The mortality at one-year follow-up was 11.9%. The 24HH was considered diagnostic in 25.2% of P (28 P), with 18.9% of all the P with necessity of pacemaker (PM) implantation. In the patients with a non-diagnostic 24HH, 6, 4% implanted a loop recorder before discharge.  Group B patients had a higher 30-day readmission rate to the ED when compared with group A (OR = 4.050 CI 95 [1.13 – 14.497], p = 0.033), but no difference in one-year readmission rate (p= 0.065). There was no difference in one-year mortality between the two groups (p= 0.731) or in one-year implantation of pacemaker (p= 0.431).  Conclusion   The use of 24HH in the ED could be a valuable tool in the diagnosis of rhythm disorders that cause syncope.  An abnormal non diagnostic result can still be a predictor of 30-day readmission to the ED with similar complaints.